1999
DOI: 10.1089/10430349950016384
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of Adenovirus-Mediated Transfer of the Human Cystic Fibrosis Transmembrane Conductance Regulator Gene to a Lung Segment of Individuals with Cystic Fibrosis

Abstract: A third-generation adenoviral vector containing recombinant human cystic fibrosis transmembrane conductance regulator (CFTR) gene was delivered by bronchoscope in escalating doses to the conducting airway of 11 volunteers with cystic fibrosis. Assessments of dose-limiting toxicity (DLT), efficiency of gene transfer, and cell-mediated and humoral immune responses to vector administration were performed. DLT, manifest by flulike symptoms and transient radiographic infiltrates, was seen at 2.1 x 10(11) total vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(62 citation statements)
references
References 19 publications
0
62
0
Order By: Relevance
“…This concept has been highlighted when demonstration of limited efficient gene transfer was obtained in human airways, as in the case of cystic fibrosis (CF) patients with both nonviral and viral vectors. [1][2][3][4] Considering only nonviral DNA delivering agents, several previous works have achieved gene transfer with cationic lipids (lipofection) and polymers (polyfection) to the lungs of laboratory animals by either direct instillation in the nose and trachea [5][6][7] or via the aerosol administration. 8,9 Systemic intravenous infusion of cationic vector/DNA complexes has been attempted and shown to transfect preferentially the lung tissue.…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been highlighted when demonstration of limited efficient gene transfer was obtained in human airways, as in the case of cystic fibrosis (CF) patients with both nonviral and viral vectors. [1][2][3][4] Considering only nonviral DNA delivering agents, several previous works have achieved gene transfer with cationic lipids (lipofection) and polymers (polyfection) to the lungs of laboratory animals by either direct instillation in the nose and trachea [5][6][7] or via the aerosol administration. 8,9 Systemic intravenous infusion of cationic vector/DNA complexes has been attempted and shown to transfect preferentially the lung tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The use of vectors based on adenovirus serotype 5, which initially showed promise, has dwindled due to the significant immunogenicity against viral capsid proteins seen in clinical trials. 14,18 Recent interest has converged on pseudotyping; be it of adeno-associated virus (AAV)-2 genomes with novel AAV serotypes 21,36 or of integrating lentiviral vectors with viral envelopes from lung pathogens. 28,29,[31][32][33]37 The Ebola virus envelope glycoprotein has been successfully used to pseudotype lentivirus and has achieved efficient transduction of the murine lung epithelium and human explants 33,34 although generation of consistently high viral titres has been problematic.…”
Section: Discussionmentioning
confidence: 99%
“…2,[13][14][15][16][17][18][19][20][21][22][23] Lentiviral vectors have the potential to integrate transgenic material into the host cell genome providing longterm expression. [24][25][26][27] However, airway epithelial gene transfer efficacy with this vector system has previously been restricted by a paucity of pseudotypes, which can be produced at high titres and which can infect lung epithelia from the apical surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of them present secondary complications and/or their use in human patients is questionable. These strategies include macrophage depletion, 39,40 use of immunosuppressive agents (cyclosporin A, cyclophosphamide, dexamethasone, FK506, Interleukin-12 and deoxypergualin), [41][42][43][44][45][46] use of antibodies to deplete CTLs, 47,48 blockade of costimulatory interactions between APCs, T and B cells, [49][50][51][52] intrathymic administration of adenovirus, 53 oral tolerization, 54 use of vectors derived from non-crossreacting serotypes, 55,56 use of adenoviruses from other species 57,58 and coating vectors with inert chemicals like polyethylene glycol (PEG). [59][60][61] Diverse in vivo studies in mice suggested that, in the absence of an immune response, first-generation adenoviral vector DNA is maintained as a stable episome in the host cell.…”
Section: Gutless Adenovirus and Immune Responsementioning
confidence: 99%